Synergistic Effect of Chemical Enhancer and Iontophoresis for Transdermal Delivery of Nebivolol Hydrochloride: Enhancement of Transdermal drug delivery - Sriram Pavani; Yamsani Madusudhan Rao; Yamsani Shravan Kumar (Iranian Journal of Pharmaceutical Sciences, 2016)
The aim of the present study was to develop and investigate the feasibility of delivering Nebivolol as a transdermal patch by iontophoresis. The passive and electrically assisted transdermal delivery of Nebivolol hydrochloride by iontophoresis will improve the therapeutic efficacy and overcome the difficulties raised in oral drug delivery. Because of its extensive hepatic metabolism and low dose, Nebivolol hydrochloride become a suitable candidate for transdermal administration. The matrix transdermal patches of Nebivolol hydrochloride were prepared and tested for in-vitro drug release and ex-vivo permeation. The study was conducted with the help of silver-silver chloride electrodes by iontophoresis across hairless rat skin. Drug release was evaluated in the presence of iontophoresis field using a current density of 0.5 mA/cm2 or without electric field i.e passive diffusion by the process of electro-migration and electro-osmosis. Drug was measured spectrophotometrically and flux was determined. The flux of Nebivolol significantly increased (P<0.05) with increase in current strength from 0.5 – 1.0 mA/cm2. The findings show that Nebivolol hydrochloride matrix transdermal therapeutic systems could be prepared with the required flux having suitable mechanical properties. It can be concluded from the results that the appliance of iontophoresis with penetration enhancer enhances the flux compared to the passive diffusion.